a)
x=4k
y=8k
z=6k
y-x=12
8k-4k=12
4k=12
k=3
x=4k=4*3=12
y=8k=8*3=24
z=6k=6*3=18
b)
x=2k
y=9k
z=5k
x*z=90
2k*5k=90
10k²=90
k²=9
k=3
x=2k=2*3=6
y=9k=9*3=27
z=5k=5*3=15
c
x=k/2
y=k/4
z=k/3
x+z=25
k/2+k/3=25
3k+2k=150
5k=150
k=30
x=k/2=30/2=15
y=k/4=30/4=7,5
z=k/3=30/3=10
d
0,6=6/10=3/5
0,(6)=6/9=2/3
0,65=65/100=13/20
x=3k/5
y=2k/3
z=13k/20
(x+y+z)/3=5,75=575/100=23/4
x+y+z=69/4
3k/5+2k/3+13k/20=69/4
36k+40k+39k=1035
115k=1035
k=1035/115=9
x=3k/5=3*9/5=5,4
y=2k/3=2*9/3=6
z=13k/20=13*9/20=5,85
e
x=k/2
y=2k/3
z=k/4
x*y*z=2/81
k/2 *2k/3 * k/4=2/81
k³/12=2/81
k³=24/81
k³=24/81=8/27
k=2/3
x=k/2=2/3 *1/2=1/3
y=2k/3=2/3 *2/3=4/9
z=k/4=2/3* 1/4=2/12